Prevalence of dental caries and its association with body mass index among school-age children in Shenzhen, China - Yi-hong Cheng; Yi Liao; Ding-yan Chen; Yun Wang; Yu Wu (BMC, 2019)
Abstract Background Dental caries and overweight/obesity are health problems with shared risk factors, but the relationships between caries and BMI need to be further explored. The objective was to evaluate the current status of dental caries and the association between dental caries and Body Mass Index (BMI) among primary and secondary school students in Shenzhen, China, during the 2016-2017 academic year. Methods A population-based, cross-sectional study that enrolled a total of 1,196,004 students was conducted in Shenzhen. Physical and dental examinations were given to all primary and secondary school students by certified physicians and dentists following the national specification for student health examinations, and dental caries was diagnosed using WHO criteria. Descriptive analysis was applied to assess current oral health status and a multifactorial, logistic regression model was employed to evaluate the relationship between dental caries and obesity. Results A total of 1,196,004 students participated in the census. Mean age of the participants was 10.3 years, ranging from 6 to 20 years. The prevalence of dental caries was 41.15% in the present study, which was higher among girls (42.88%) than that in boys (39.77%) with a p-value of < 0.001. Students in public schools showed a significantly lower (p < 0.001) caries prevalence (37.36%) compared with those in private schools (47.96%). The caries restoration rate of students in Shenzhen was only 10.30%, which means only one out of ten students with caries received restorations. The mean dmft and DMFT scores were 0.97 and 0.33, respectively. More girls (10.96%) had their teeth filled than boys (9.78%). The restoration rate was higher (p < 0.001) in public schools (11.73%) than in private ones (8.35%). Children who were overweight or obese had a lower risk of experiencing caries compared to those who were within a normal weight (OR = 0.74/0.64). Caries was inversely associated with BMI among primary and secondary school students in Shenzhen. Conclusions The prevalence of dental caries among primary and secondary school children was found to be related to sex, type of schools, region, and BMI. Further studies and more government support are required to confirm the findings of this study and to address current oral health problems.